Antithrombotic Agents after Free Tissue Transfer in the Pediatric and Adolescent Population - Weiss, Jakob B.W.; Kollár, Branislav; Eisenhardt, Steffen U. (Journal of Reconstructive Microsurgery, 2024)
Even for the experienced microsurgeon, free tissue transfer in pediatric patients is challenging, and large patient series remain scarce in the literature. Moreover, the added value of antithrombotic agents in pediatric free tissue transfer remains unclear.We conducted a retrospective outcome analysis of pediatric free tissue transfer with respect to postoperative antithrombotic treatment at our tertiary academic center. All patients aged 0 to 18 years who underwent free tissue transfer from 1998 to 2022 were included in the study.Seventy patients received 73 free tissue transfers. The most common indications were facial paralysis, trauma, and tumor (49.3, 21.9, and 20.5%, respectively). The most common recipient sites were the head and neck (56.1%) and lower extremity (32.8%). We observed a flap revision rate of 12.5% of the cases and one flap loss (1.4%). A total of 58.9% of the population received postoperative antithrombotic agents. The rate of flap revision surgery was similar (11.6 and 10.0%, respectively), with and without antithrombotic treatment (p > 0.05). There were no major bleeding complications or deep vein thrombosis.The antithrombotic treatment did not seem to affect the flap revision rate or the bleeding complications in our cohort. Hence, the data do not support the routine administration of antithrombotic treatment in pediatric free flap reconstruction. However, these findings should be solidified in prospective randomized trials.
Keywords: microsurgery; pediatric reconstructive surgery; antithrombotics